AB0514 Efficacy and Safety of Tofacitinib in Chinese Patients with Active Rheumatoid Arthritis: Subgroup Analysis from a Phase 3 Study of Tofacitinib in Combination with Nonbiologic Disease-Modifying Antirheumatic Drugs. (9th June 2015) - An, Y.; Li, Z.; Wu, Q.; Kwok, K.; Wang, L.
Abstract : Background: Tofacitinib is an oral Janus kinase inhibitor for the treatment of rheumatoid arthritis (RA). In the global Phase 3 ORAL Sync study (NCT00856544 ), tofacitinib improved disease activity in patients (pts) who had active RA despite treatment with nonbiologic disease-modifying antirheumatic drugs (DMARDs). 1 Objectives: To report a post-hoc analysis of efficacy and safety in a subgroup of Chinese pts. Methods: ORAL Sync was a 1-year, double-blind, placebo-controlled, parallel-group study. Pts (N=795) with active RA were randomised 4:4:1:1 to oral tofacitinib 5 or 10 mg twice daily (BID), or placebo advanced to tofacitinib 5 or 10 mg BID at 3 (nonresponders) or 6 (remaining pts) months. All pts remained on ≥1 background nonbiologic DMARD throughout. Co-primary efficacy endpoints were ACR20 response rate at Month 6 (M6), change from baseline in physical function (HAQ-DI) at M3, and proportion of pts achieving DAS28-4(ESR)<2.6 at M6. Efficacy and safety outcomes in the subgroup of pts from 20 centres in China vs the global study population are reported; post-hoc tests for statistical significance were performed. Results: In total, 792 pts were treated (global population), including 216 Chinese pts. Baseline demographics were similar across treatment groups in the Chinese population (n=86 tofacitinib 5 mg BID; n=86 tofacitinib 10 mg BID; n=44 placebo; 85% female; mean age, 48 years). Both tofacitinib doses demonstrated significant improvements vs placebo in ACR20 response rate at M6 in Chinese pts (p≤0.0001). ACR20 response rates at M6 were numerically higher with tofacitinib in Chinese pts vs the global population (Table ). Numerically more Chinese pts achieved DAS28-4(ESR)<2.6 with tofacitinib 5 and 10 mg BID vs placebo at M6, which was significant with the 10 mg BID dose (p=0.1803 and p=0.0120 with tofacitinib 5 and 10 mg BID, respectively; Table ). Both tofacitinib doses also demonstrated significant improvements in HAQ-DI at M3 in Chinese pts; least squares (LS) mean difference (95% CI) vs placebo was -0.23 (-0.40, -0.05; p=0.0137) and -0.35 (-0.53, -0.17; p=0.0002) with tofacitinib 5 and 10 mg BID, respectively. Tofacitinib efficacy was generally sustained over 12 months. The most frequently reported adverse events (AEs) were upper respiratory tract infection, elevated aminotransferases, and leukopenia. Incidence of AEs, serious AEs (SAEs), AE discontinuations, serious infections and herpes zoster infections over M0–3 are reported in the Table . SAEs over M3–6 and after M6 were reported in 2 (1.2%) Chinese pt with tofacitinib 10 mg BID. Conclusions: Tofacitinib, in combination with background DMARDs, significantly improved signs and symptoms and improved physical function vs placebo over 1 year in Chinese pts with active RA. Efficacy and safety findings in the Chinese subgroup were consistent with the global population. References: Kremer J et al. Ann Intern Med 2013; 159: 253-261. Acknowledgements: All aspects of this work were funded by Pfizer Inc. Editorial support, under the direction of the authors, was provided by Amanda Pedder of Complete Medical Communications, and funded by Pfizer Inc. Disclosure of Interest: Y. An: None declared, Z. Li: None declared, Q. Wu Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, K. Kwok Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, L. Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc